The Concept of Social Justice and Integrity in Testimony according to Islam: A Thematic Study of Surah Al-Maidah Verse 8 - Dinningrum, Khairani Makina; Dahliana, Yeti (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
This article discusses the principles of upholding social justice from the perspective of the Qur'an, focusing on the interpretation of Surah Al-Maidah, verse 8. This verse emphasizes the importance of fairness, both in personal and social matters, requiring Muslims to be objective and not influenced by hatred or animosity. In this context, justice is not only viewed in terms of fair punishment or decision-making, but also in how individuals treat others without discrimination. The interpretation of this verse contains universal values that are relevant in addressing contemporary challenges, such as the protection of human rights, equality, and the maintenance of peace. The research method employed in this study is the library research method, which is a type of research based on library resources. In this approach, the researcher utilizes sources of data that are relevant to the subject matter being investigated. Through both classical and contemporary interpretation, this study aims to explore the profound moral and ethical messages in upholding social justice as conveyed by Allah SWT. The findings show that the Qur'an stresses the importance of justice that prioritizes balance and avoids oppression, while offering guidance for believers to act responsibly in all aspects of life.